Emerging 2D Materials Produced via Electrochemistry - Yang, Sheng; Zhang, Panpan; Nia, Ali Shaygan; Feng, Xinliang (Advanced Materials, 2020)
2D materials are important building blocks for the upcoming generation of nanostructured electronics and multifunctional devices due to their distinct chemical and physical characteristics. To this end, large-scale production of 2D materials with high purity or with specific functionalities represents a key to advancing fundamental studies as well as industrial applications. Among the state-of-the-art synthetic protocols, electrochemical exfoliation of layered materials is a very promising approach that offers high yield, great efficiency, low cost, simple instrumentation, and excellent up-scalability. Remarkably, playing with electrochemical parameters not only enables tunable material properties but also increases the material diversities from graphene to a wide spectrum of 2D semiconductors. Here, a succinct and critical survey of the recent progress in this research direction is presented, comprising the strategic design, exfoliation principles, underlying mechanisms, processing techniques, and potential applications of 2D materials. At the end of the discussion, the emerging trends, challenges, and opportunities in real practice are also highlighted.
CRIS-Team Scopus Importer:2023-03-20
Keywords: 2D materials; black phosphorus; graphene; MXene; transition metal dichalcogenides